Community Development Through Activities Teaching Religious Education to Children at SDN 2 Arahan Lor - Tiya Lestari (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2023)
The main objective of KKN is to enable students to directly apply the knowledge they have acquired in the field of education to the community. KKN also serves as a means for students to gain broader insights into knowledge and experiences within society. From the observations made, issues have been identified among adolescents and the community in Desa Arahan Lor, namely the scarcity of highly educated individuals and the lack of religious knowledge. Additionally, the lack of education has resulted in a deficiency in understanding and practicing religious activities. To address these issues, a program titled "The Importance of Teaching Religious Education to Children" is proposed. This program aims to provide added value to the community, including motivating them to learn. In its implementation, the program will utilize methods such as lectures, discussions, and thorough sharing at SDN 2 Arahan Lor to enhance the comprehension and sensitivity towards religion among young children.